Properties and microstructure of total tailings cemented paste backfill material containing mining and metallurgical solid waste - Wang, Changlong; Qi, Yang; Jing, Jianlin; Ma, Jintao; Zhou, Yongxiang; Ping, Haoyan; Zheng, Yongchao; Zhai, Yuxin; Liu, Feng (Frontiers in Earth Science, 2023)
Introduction: In order to improve the utilization efficiency of industrial waste discharged in the process of iron and steel metallurgy, a kind of material that can replace cement for mine filling is sought. In the test, steel slag (SS) and vanadium-titanium slag (VTS) were used as the primary raw materials to prepare cementing agents (CA). Then, combine it with vanadium-titanium iron ore tailings (VTIOTs) to make mine cemented paste backfill material (CPBM). Methods: The composition, properties and hydration mechanism of CPBM are studied through various tests, in-cluding mechanical property test, hydration heat test, X-ray diffraction (XRD), scanning electronic mi-croscopy (SEM), and fourier transform-infrared spectroscopy (FT-IR). Results: The results show that when the following conditions are met, the slump is 216 mm, and the 28-day flexural strength and compressive strength of CPBM reach 4.25 and 9.41 MPa, respectively, which meets the requirements of Chinese National Standard GB/T 39489-2020 Technical specification for the total tailings paste backfill: the mass percentage SS: VTS: phosphogypsum (PG): dicyandiamide waste slag (DWS) = 31:59:6:4; the content of compound phosphoric acid (CPA) accounts for 4% of the dry material; the cement sand ratio of CPBM is 1:4; the paste mass concentration (PMC) is 80%; and the content of water reducing agent (WRA) is 0.18%. Discussion: Mechanism studies show that the hydration product of the CA is mainly ettringite (AFt) and C-S-H gel. The addition of CPA promotes the hydration of active minerals in SS and VTS. The existence of PG pro-motes the formation of AFt, and the formation of AFt further promotes the fracture of [AlO4]5− and [SiO4]4− along the bridge oxygen in VTS and SS.